Impact of daily lifestyle on coronary heart disease - WAN, YAN-FANG (Exp Ther Med, 2015)
Limited data are available with regard to the impact of daily lifestyle choices in patients with coronary heart disease (CHD) who have undergone stent placement. Thus, the aim of the present study was to investigate the impact of daily lifestyle factors in patients with CHD following stent implantation. Between March 2005 and March 2006, 129 consecutive patients with CHD were admitted to Cangzhou Central Hospital at Hebei Medical University (Cangzhou, China). The patients underwent coronary stenting and participated in a 7-year clinical follow-up that analyzed the impact of their daily lifestyle choices on CHD following the stent placement. Rates of dinner satiety [95% confidence interval (CI), 1.121–10.97, P=0.005], smoking (95% CI, 4.05–34.90, P=2.01×10(−7)) and heavy alcohol use (95% CI, 1.32–11.05, P=0.006) were significantly higher in the repeated (re)-revascularization group when compared with the non-revascularization group. In addition, the exercise rate was significantly lower in the re-revascularization group when compared with the non-revascularization group (95% CI, 0.02–0.65, P=0.005). However, no statistically significant differences were observed between the groups with regard to sleeping patterns (95% CI, 0.03–0.71, P=0.270) or anxiety rates (P=0.289). A coronary angiography performed during re-revascularization revealed in-stent restenosis in 26% of the patients, stenoses at the entrance to or exit from the stent in 29% of the patients and new lesions in 19% of the patients. Furthermore, original lesions exhibited deterioration in 26% of the patients. The clinical endpoint was reached in 55% of the patients between 3 and 5 years of the follow-up period. In conclusion, poor daily lifestyle habits can increase the in-stent restenosis rate, accelerate the progression of the original lesion and promote the emergence of new lesions in patients with CHD following stent placement.